2015
DOI: 10.12659/msm.896274
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanics of Artificial Disc Replacements Adjacent to a 2-Level Fusion in 4-Level Hybrid Constructs: An In Vitro Investigation

Abstract: BackgroundThe ideal procedure for multilevel cervical degenerative disc diseases remains controversial. Recent studies on hybrid surgery combining anterior cervical discectomy and fusion (ACDF) and artificial cervical disc replacement (ACDR) for 2-level and 3-level constructs have been reported in the literature. The purpose of this study was to estimate the biomechanics of 3 kinds of 4-level hybrid constructs, which are more likely to be used clinically compared to 4-level arthrodesis.Material/MethodsEighteen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Briefly, the original form of this protocol consisted of (a) applying pure moments to intact spine, (b) applying pure moments to implanted spine until its ROM is equal to the ROM of the intact spine (i.e., results from the previous step), and (c) the statistical comparison of the biomechanical variables in the two conditions. This motion-controlled moment loading was selected to simulate the clinical setting related to the total motion of the cervical spine [30][31][32][33]. A force of 73.6 N was applied to the upper surface of the C2 vertebral body, 1.5 N/M was applied in the X-axis direction according to the right-hand rule, and a moment of 1.0 N/M was applied to the Y-axis and Z-axis to simulate the flexion, extension, left/right lateral bending, and left/right axial rotation of the cervical spine.…”
Section: Finite Element Analysis (Fea) Model Establishmentmentioning
confidence: 99%
“…Briefly, the original form of this protocol consisted of (a) applying pure moments to intact spine, (b) applying pure moments to implanted spine until its ROM is equal to the ROM of the intact spine (i.e., results from the previous step), and (c) the statistical comparison of the biomechanical variables in the two conditions. This motion-controlled moment loading was selected to simulate the clinical setting related to the total motion of the cervical spine [30][31][32][33]. A force of 73.6 N was applied to the upper surface of the C2 vertebral body, 1.5 N/M was applied in the X-axis direction according to the right-hand rule, and a moment of 1.0 N/M was applied to the Y-axis and Z-axis to simulate the flexion, extension, left/right lateral bending, and left/right axial rotation of the cervical spine.…”
Section: Finite Element Analysis (Fea) Model Establishmentmentioning
confidence: 99%
“…Then, we determined the bending moment in both modes to each CDA spine that matched the ROM determined in the pure moment condition for the intact spine. In other words, the hybrid moment protocol was followed in the present study, a protocol also used in other studies [18][19][20][21]. While CDAs are used in the military, impact loads should be studied because the population is subjected to activities involving higher g-forces, routinely [22,23].…”
Section: Loading and Output Parametersmentioning
confidence: 99%
“…The decompression of the spinal cord and nerve roots usually requires the removal of some structures that maintain spinal stability, such as the lamina and facet process, which changes the biomechanics of the adjacent segments. Previous research has shown that the fusion and fixation of the moving segments increases the stress of the adjacent segments at the cephalic side [ 27 ]. Smith Robinson et al conducted finite element analysis after spinal fusion surgery, which also showed that the internal stress of the cephalic segment increased [ 28 ].…”
Section: Discussionmentioning
confidence: 99%